Comparative Technoeconomic Analysis of Using Waste and Virgin Cooking Oils for Biodiesel Production - Al-Sakkari, Eslam G.; Mohammed, Mohammed G.; Elozeiri, Alaaeldin A.; Abdeldayem, Omar M.; Habashy, Mahmoud M.; Ong, Ee Shen; Rene, Eldon R.; Ismail, Ibrahim; Ashour, Ibrahim (Frontiers in Energy Research, 2020)
This study aims to provide the technoeconomic aspects of two clean processes for biodiesel production. The first process utilizes waste cooking oil as a feedstock and potassium hydroxide as a homogeneous catalyst. The second process uses cement kiln dust heterogeneous catalyst and virgin soybean oil. A comparison was performed between the results of the technical and economic assessments to determine the more feasible process. Theoretical purities of biodiesel and glycerol obtained upon conducting the simulation of both processes are high, i.e., 99.99%. However, the homogeneous process is economically superior as its payback period is slightly more than 1 year while the return on investment is higher than 74%, and the unit production cost is USD 1.067/kg biodiesel. Sensitivity analysis revealed that the profitability of biodiesel production is very sensitive to the feedstock price and recommends shifting toward waste vegetable oils as a cheap feedstock to have a feasible and economic process.